Radium-223 for the treatment of metastatic castration-resistant prostate cancer (mCRPC): The androgen receptor-independent active agent in the therapeutic sequence Radium-223 zur Therapie des metastasierten kastrationsresistenten Prostatakarzinoms (mCRPC): Der androgenrezeptorunabhängige Wirkstoff in der therapeutischen Sequenz - König, F.; Strauß, A.; Johannsen, M.; Mommsen, C.; Fricke, E.; Klier, J.; Mehl, S.; Pfister, D.; Sahlmann, C. O.; Werner, A.; Goebell, Peter (Urologe, 2019)
Background: Radium-223 improves overall survival and preserves quality of life in patients with metastatic castration-resistant prostate cancer (mCRPC) and symptomatic bone metastases and no known visceral metastases. Radium-223 can be used in combination with a luteinizing hormone releasing hormone (LHRH) analogue and as part of a sequential treatment scheme if disease progresses after at least two prior lines of systemic mCRPC therapies or if no other available systemic treatment is eligible. Objectives: Today physicians are faced with a previously unknown multitude and complexity of options for the treatment of mCRPC. An increasing number of clinical trials contribute to the dynamics of the therapeutic landscape. Radium-223 was approved for mCRPC treatment in 2013. Up to now the recommendations of use have been adjusted several times. Highlighting recent clinical trials and practice, this paper explores the position of radium-223 within the therapeutic sequence and outlines key elements for the interdisciplinary cooperation between uro-oncologists and nuclear medicine specialists. Results: The mode of action of radium-223 does not depend on the androgen receptor (AR) pathway. Thus, it is an option in the therapeutic sequence when the efficacy of other agents is reduced by resistance. Furthermore, the efficacy of prior or subsequent medications are neither reduced nor enhanced by radium-223. The opportunity of an AR-independent and survival-prolonging medication should be taken as soon as the indication criteria are met because the incidence of visceral metastases increases during disease progression. According to current mCRPC guidelines, the osteoprotective use of bisphosphonates or denosumab is recommended, before treatment with radium-223 is started or resumed.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Bone metastases; Castration resistance; Prostate cancer; Radium-223; Therapeutic sequence